Role of export industries in the economy of Latin America - W. P. Chavarry Galvez (Вестник университета)
The article examines the role of export industries in the economy of Latin America at the present stage. The study identified the GDP growth rates of the countries of this region, the comparison of the total GDP of Latin America with the world, the economic potential of the region, the main developing sectors of the economies of Latin America, the methods of countries ‘ recovery from the economic crisis, the main points of growth and potentials. The analysis made it possible to identify problems and identify ways to solve them at the state level, to identify countries with the most dynamically developing economies and the reasons for increasing their competitiveness in the world market.